Optimization of Molecularly Imprinted Poly (MAA-co-AM) Composite Membranes for Evaluation of Chlorimuron-Ethyl Herbicide - Li, Xiao-Liu; Liu, Zheng-Hao; Lv, Yun-Kai; Gao, Jun-Gang; Zhai, Xue-Fei; Huang, Ya-Jing (Asian Journal of Chemistry, 2013)
Several experimental conditions, such as reaction solvent, extraction solvent, extraction time and crosslinker were evaluated and optimized in the preparation molecularly imprinted composite membranes using chlorimuron-ethyl herbicide as the template. The structures and the thermal stability of molecularly imprinted composite membranes were characterized by infrared spectroscopy and thermogravimetric analysis. The static equilibrium binding properties of the membranes to chlorimuron-ethyl and the swelling property of the membrane in different solvents were tested. The Scatchard plot revealed that one class of binding sites was mainly produced in the imprinted composite membrane in the studied concentration range of chlorimuron-ethyl herbicide.